The Implementation of Gamification to Enhance Students’ Vocabulary at one of Junior High School in Jakarta - Nadiyah, Indah Firah; Sadikin, Irma Savitri (IKIP Siliwangi, 2026)
This study aims to investigate how the use of gamification to improve students’ vocabulary at ninth grade in one of Junior High School Jakarta. The researcher employed a Classroom Action Research (CAR) approach created by Kemmis and McTaggart (2014). This study was conducted in 2 cycles where each cycle consists of four steps: planning, action, observation, and reflection. The researcher collected data using both qualitative (observation) and quantitative (pre-test and post-test) methods. The results of this study found that the use of gamification increased the students’ vocabulary. The pre-test revealed a mean score of 66.8, with only 43.3% of students exceeding the Minimum Competency Standards (KKM). After the first cycle of implementing Baamboozle, the mean score increased to 77.1, with 66.6% of students meeting or exceeding the KKM. In the second cycle, the mean score further improved to 83.2, with 86.6% of students achieving minimum competency. These results demonstrate a significant positive impact of gamification on students' vocabulary acquisition in the learning process.